A Rare Cause of Heart Failure Treated by Heart Transplantation: Noncompaction of the Ventricular Myocardium - Julien Bordes; Bertrand Jop; Sandrine Imbert; Sami Hraiech; Frédéric Collard; François Kerbaul (Case Reports in Medicine)
Noncompaction of the ventricular myocardium is a rare cardiomyopathy due to an arrest of myocardial morphogenesis. The characteristic echocardiographic findings are prominent myocardial trabeculations and deep intertrabecular spaces communicating with the left ventricular cavity. The clinical manifestations include heart failure (HF) signs, ventricular arrhythmias, and cardioembolic events. We describe an illustrative case of noncompaction of the ventricular myocardium associated with bicuspid aortic valve, a 42-year-old male presenting a refractory acute heart failure successfully treated by emergency heart transplantation.